REVIEW OF NEUTRACEUTICAL APPROACH TO FIGHT CANCER CAUSING ELEMENTS: A PERCEPTORY VIEW - Dr. Kamla R. Nagar Dr. Rakesh K. Nagar (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2018)
Cancer is the most feared of all disease. Cancer is a proliferation of cells in the body which undergo unregulated growth. These cells often spread by seeding themselves though out the body. Typically growing in the form of tumors, new tumors emerge as cells take root and grow in different parts of the body. Classical Ayurvedic texts have several references to cancer. It has an integrated approach to the prevention and treatment of illness and tries to maintain or re-establish the harmony between the mind, body, and forces of nature. It combines a number of approaches, such as changes in lifestyle, herbal remedies, exercise, and meditation to strengthen and purify the body and mind and increase spiritual awareness. Ayurvedic knowledge about diet is quite extensive and patients should follow a diet appropriate to their prakruti and vikruti. Herbs offer great potential to stimulate the healing process and can even destroy cancer cells. This property of an herb (or drug) is called the cytotoxic effect. Dietary patterns, foods, nutrients, and other dietary constituents are closely associated with the risk for several types of cancer,35 percent of cancer deaths may be related to dietary factors. Evidence suggests that diets high in fiber- containing foods are associated with a reduced risk for cancer,of the breast, colon. Studies have also shown a reduced risk of cancer with diets rich in fruits, vegetables and grain products, carotenoids, vitamin-C. A leaner diet is believed to lower cancer risk. Tomatoes, calcium, other minerals, saponins, are believed to prevent or suppress different kinds of cancer.